Perspectives of traditional herbal medicines in treating retinitis pigmentosa - Liu, Shihui; Matsuo, Toshihiko; Matsuo, Chie; Abe, Takumi; Chen, Jinghua; Sun, Chi; Zhao, Qing (Frontiers in Medicine, 2024)
Medicinal plants, also known as herbs, have been discovered and utilized in traditional medical practice since prehistoric times. Medicinal plants have been proven rich in thousands of natural products that hold great potential for the development of new drugs. Previously, we reviewed the types of Chinese traditional medicines that a Tang Dynasty monk Jianzhen (Japanese: Ganjin) brought to Japan from China in 742. This article aims to review the origin of Kampo (Japanese traditional medicine), and to present the overview of neurodegenerative diseases and retinitis pigmentosa as well as medicinal plants in some depth. Through the study of medical history of the origin of Kampo, we found that herbs medicines contain many neuroprotective ingredients. It provides us a new perspective on extracting neuroprotective components from herbs medicines to treat neurodegenerative diseases. Retinitis pigmentosa (one of the ophthalmic neurodegenerative diseases) is an incurable blinding disease and has become a popular research direction in global ophthalmology. To date, treatments for retinitis pigmentosa are very limited worldwide. Therefore, we intend to integrate the knowledge and skills from different disciplines, such as medical science, pharmaceutical science and plant science, to take a new therapeutic approach to treat neurodegenerative diseases. In the future, we will use specific active ingredients extracted from medicinal plants to treat retinitis pigmentosa. By exploring the potent bioactive ingredients present in medicinal plants, a valuable opportunity will be offered to uncover novel approaches for the development of drugs which target for retinitis pigmentosa.